Efficacy of Plasma-Treated Water against Salmonella Typhimurium: Antibacterial Activity, Inhibition of Invasion, and Biofilm Disruption - Adrian Abdo; Andrea McWhorter; Daniel Hasse; Thomas Schmitt-John; Katharina Richter (MDPI AG, 2023)
Plasma-treated water (PTW) has emerged as a potential sanitizing agent. This study evaluated antibacterial activity, inhibition of invasion, and biofilm disruption effects of PTW against Salmonella Typhimurium. Minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) were determined for different PTW types. Time-kill assays were conducted to assess bactericidal effects, while polarized Caco-2 cells were used to evaluate invasion inhibition. Biofilm formation and cell viability were examined following PTW treatment using Salmonella Typhimurium isolates, while biofilm disruption and regrowth prevention were investigated using the Bioflux system. PTW exhibited antibacterial activity against all Salmonella Typhimurium isolates, with MICs of 25% for PTW1 and PTW2, and 50% for PTW3, PTW4, and PTW5. MBCs of 50% in media were observed for all PTW types. Undiluted PTW1 and PTW2 showed the highest bactericidal capacity, significantly reduced Salmonella viability, and completely inhibited bacterial invasion, while PTW3 and PTW5 also showed significant invasion reduction. Bioflux experiments confirmed the eradication of biofilms by PTW1 and PTW2, with no regrowth observed 72 h after PTW was removed. PTW demonstrated significant antibacterial activity, inhibition of invasion, biofilm disruption, and reduction of bacterial viability against Salmonella Typhimurium. This highlights PTW's potential as an effective sanitizer for reducing Salmonella contaminations.